2016
DOI: 10.1016/j.jadohealth.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

School-Based Protective Factors Related to Suicide for Lesbian, Gay, and Bisexual Adolescents

Abstract: Background: Research indicates that lesbian, gay, and bisexual (LGB) adolescents are three

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 27 publications
1
51
2
1
Order By: Relevance
“…Third, online resources (eg, online sex education websites) should be integrated to provide more relevant information and education, which may help to foster a more tolerant and open atmosphere towards sexual minorities. Fourth, families and communities should provide social support (eg, Gay–Straight Alliance groups, and Parents and Friends of Lesbians and Gays) to promote acceptance of sexual minority orientation 53 and reduce pressure from traditional values and norms embedded in Confucianism (eg, filial piety and family responsibilities). 51 Fifth, practitioners (eg, psychologists, psychiatrists, counsellors and social workers) should specifically focus on the group that is at particularly high risk of suicidality (ie, BSA adolescents) with a weaker collective identity.…”
Section: Discussionmentioning
confidence: 99%
“…Third, online resources (eg, online sex education websites) should be integrated to provide more relevant information and education, which may help to foster a more tolerant and open atmosphere towards sexual minorities. Fourth, families and communities should provide social support (eg, Gay–Straight Alliance groups, and Parents and Friends of Lesbians and Gays) to promote acceptance of sexual minority orientation 53 and reduce pressure from traditional values and norms embedded in Confucianism (eg, filial piety and family responsibilities). 51 Fifth, practitioners (eg, psychologists, psychiatrists, counsellors and social workers) should specifically focus on the group that is at particularly high risk of suicidality (ie, BSA adolescents) with a weaker collective identity.…”
Section: Discussionmentioning
confidence: 99%
“…However, the few studies that do exist are promising. For example, several school characteristics have been associated with lower risk for suicidal ideation among same-sex attracted youth, such as having a supportive teacher and a strong sense of school community (Russell & Toomey, 2013;Whitaker, Shapiro, & Shields, 2016). Further, high social support has been linked to lower LGB youth distress (McConnell, Birkett, & Mustanksi, 2015;Snapp, Watson, Russell, Diaz, & Ryan, 2015), and, in particular, parent support is associated with lower risk for suicidal behavior (Ryan, Russell, Huebner, Diaz, & Sanchez, 2010).…”
Section: Risk and Protection Of Suicidal Behaviors By Sexual Orientationmentioning
confidence: 99%
“…Previous research has shown that protective school environments provide LGBTQ+ students with significant benefits [48]. Connectedness at school is associated with caring interpersonal relationships, engaged participation in activities, better academic outcomes, and lower suicidal ideation among this group of students [12,49,50]. Policies that curtail victimization in schools have also proven to have positive outcomes such as fewer incidences of suicide attempts and bullying [51,52].…”
Section: Better School Environmentmentioning
confidence: 99%